2018
DOI: 10.1088/0256-307x/35/11/110303
|View full text |Cite
|
Sign up to set email alerts
|

Exact Equivalence between Quantum Adiabatic Algorithm and Quantum Circuit Algorithm

Abstract: We present a rigorous proof that quantum circuit algorithm can be transformed into quantum adiabatic algorithm with the exact same time complexity. This means that from a quantum circuit algorithm of L gates we can construct a quantum adiabatic algorithm with time complexity of O(L). Additionally, our construction shows that one may exponentially speed up some quantum adiabatic algorithms by properly choosing an evolution path.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…An important discovery by Yu et al (2018) shows that the adiabatic and gate systems offer effectively the same potential for achieving the gains inherent in quantum computing processes, with a mathematical demonstration that the quantum circuit algorithm can be transformed into the quantum adiabatic algorithm with the exact same time complexity. This has useful implications for the relevance of QUBO models that have been implemented in an adiabatic quantum annealing setting, disclosing that analogous advances associated with QUBO models may ultimately be realized through quantum circuit systems.…”
Section: Y = 2588mentioning
confidence: 99%
“…An important discovery by Yu et al (2018) shows that the adiabatic and gate systems offer effectively the same potential for achieving the gains inherent in quantum computing processes, with a mathematical demonstration that the quantum circuit algorithm can be transformed into the quantum adiabatic algorithm with the exact same time complexity. This has useful implications for the relevance of QUBO models that have been implemented in an adiabatic quantum annealing setting, disclosing that analogous advances associated with QUBO models may ultimately be realized through quantum circuit systems.…”
Section: Y = 2588mentioning
confidence: 99%
“…Como o teorema da equivalência entre os dois paradigmas de computação quântica prevê que os dois são análogos [30,44], foi encontrado uma versão adiabática para o algoritmo de busca, que chamaremos de algoritmo de Grover adiabático [45,46]. Nele, a análise de complexidade, se dá no tempo de evolução do Hamiltoniano, queé proporcionalà raiz quadrada do número de itens no banco de dados, assim τ max ∝ √ N .…”
Section: Algoritmo De Grover Adiabáticounclassified
“…In the adiabatic algorithm, the quantum computer follows the ground state of a time-dependent Hamiltonian. It has been shown that every quantum circuit algorithm can be converted into a quantum adiabatic algorithm, whose time complexity is exactly the same [6,7]. A quantum Hamiltonian algorithm for independent-set problems has some advantages over other known quantum algorithms and classical algorithms [8].…”
Section: Introductionmentioning
confidence: 99%